Alternative account: User:Beneficii
Basic definition of a sum
[edit ]
{\displaystyle \sum _{i=m}^{n}{\mathit {f}}(i)={\mathit {f}}(m)+{\mathit {f}}(m+1)+{\mathit {f}}(m+2)+,円...,円+{\mathit {f}}(n-2)+{\mathit {f}}(n-1)+{\mathit {f}}(n),円}
Where {\displaystyle p\geq 0}:
{\displaystyle \sum _{i=m}^{i_{p}}\!{}^{p}\ f(i)=\sum _{i_{p-1}=m}^{i_{p}},円\sum _{i_{p-2}=m}^{i_{p-1}},円\sum _{i_{p-3}=m}^{i_{p-2}}...\sum _{i_{2}=m}^{i_{3}},円\sum _{i_{1}=m}^{i_{2}},円\sum _{i_{0}=m}^{i_{1}}f(i_{0}),円}
{\displaystyle \sum _{i=m}^{i_{0}}\!{}^{0}\ {\mathit {f}}(i)={\mathit {f}}(i_{0}),円}
{\displaystyle \sum _{i=m}^{i_{1}}\!{}^{1}\ {\mathit {f}}(i)=\sum _{i_{0}=m}^{i_{1}}{\mathit {f}}(i_{0}),円}
{\displaystyle \mathrm {If\ } {\mathit {g}}(n)=\sum _{i=m}^{n}\!{}^{-p},円{\mathit {f}}(i),\ \mathrm {then\ } {\mathit {f}}(n)=\sum _{i=m}^{n}\!{}^{p},円{\mathit {g}}(i).,円}
Where {\displaystyle p>0}:
{\displaystyle \sum _{i=m}^{i_{p}}\!{}^{p}\ {\mathit {f}}(i)=\sum _{i_{p-1}=m}^{i_{p}}\left[\sum _{i=m}^{i_{p-1}}\!{}^{p-1},円{\mathit {f}}(i)\right],円}
{\displaystyle \sum _{i_{p-1}=m}^{i_{p}}\left[\sum _{i=m}^{i_{p-1}}\!{}^{p-1},円{\mathit {f}}(i)\right]=\sum _{i=m}^{m}\!{}^{p-1},円{\mathit {f}}(i)+\sum _{i=m}^{m+1}\!{}^{p-1},円{\mathit {f}}(i)+\sum _{i=m}^{m+2}\!{}^{p-1},円{\mathit {f}}(i)+,円...+,円\sum _{i=m}^{i_{p}-2}\!{}^{p-1},円{\mathit {f}}(i)+\sum _{i=m}^{i_{p}-1}\!{}^{p-1},円{\mathit {f}}(i)+\sum _{i=m}^{i_{p}}\!{}^{p-1},円{\mathit {f}}(i),円}
Shifting of starting and ending indices
[edit ]
{\displaystyle \sum _{i=m}^{n}{\mathit {f}}(i)=\sum _{i=m+u}^{n+u}{\mathit {f}}(i-u),円}
Proof of the equality of the shifting of indices:
[edit ]
{\displaystyle ,円\!{\begin{array}{lcl}\sum _{i=m+u}^{n+u}{\mathit {f}}(i-u)&=&{\mathit {f}}((m+u)-u)+{\mathit {f}}((m+u+1)-u)+{\mathit {f}}((m+u+2)-u)\\&&+,円...,円+{\mathit {f}}((n+u-2)-u)+{\mathit {f}}((n+u-1)-u)+{\mathit {f}}((n+u)-u)\\\\&=&{\mathit {f}}(m)+{\mathit {f}}(m+1)+{\mathit {f}}(m+2)+,円...,円+{\mathit {f}}(n-2)+{\mathit {f}}(n-1)+{\mathit {f}}(n)\\\\&=&\sum _{i=m}^{n}{\mathit {f}}(i)\end{array}},円}
Smaller summation notation
[edit ]
{\displaystyle ,円\!\sum _{i=m}^{n}\!{}^{p}\ {\mathit {f}}(i)=\textstyle \!{}_{p}\!\sum _{i=m}^{n}{\mathit {f}}(i),円}
{\displaystyle ,円\!{\begin{array}{lcl}{}_{p}\!\sum _{i=m}^{n}r^{i}&=&{r^{n+p} \over (r-1)^{p}}-\sum _{k=0}^{p-1}{r^{m+p-(k+1)}\prod _{j=1}^{k}(n-m+j) \over k!(r-1)^{p-k}}\\&=&{r^{n+p} \over (r-1)^{p}}-\sum _{k=0}^{p-1}{r^{m+p-(k+1)}{(n-m+k)! \over (n-m)!} \over (r-1)^{p-k}k!}\\&=&{r^{n+p} \over (r-1)^{p}}-\sum _{k=0}^{p-1}\left({r^{m+p-(k+1)} \over (r-1)^{p-k}}\right){{n-m+k} \choose k}\end{array}},円}
Combinations proof (used in below proof)
[edit ]
{\displaystyle \mathrm {For\ non-negative\ integers\ } q\ \mathrm {and\ } t\geq q,\quad \sum _{z=q}^{t}{z \choose q}={t+1 \choose q+1}.,円}
{\displaystyle t=q,\quad \sum _{z=q}^{q}{z \choose q}={q \choose q}=1={q+1 \choose q+1},円}
{\displaystyle t=c,\quad \sum _{z=q}^{c}{z \choose q}={c+1 \choose q+1},円}
{\displaystyle t=c+1,\quad \sum _{z=q}^{c+1}{z \choose q}=\sum _{z=q}^{c}{z \choose q}+{c+1 \choose q}={c+1 \choose q+1}+{c+1 \choose q}={(c+1)+1 \choose q+1},円}
{\displaystyle \mathrm {For\ a\ real\ number\ } r\neq 1\ \mathrm {and\ non-negative\ integers\ } m,\ p,\ \mathrm {and\ } i_{p},\ \mathrm {where\ } i_{p}\geq m,}
{\displaystyle \sum _{i=m}^{i_{p}}\!\!{}^{p},円r^{i}={r^{i_{p}+p} \over (r-1)^{p}}-\sum _{k=0}^{p-1}{r^{m+p-(k+1)}\prod _{j=1}^{k}(i_{p}-m+j) \over k!(r-1)^{p-k}}.,円}
Base case (and some specific examples)
[edit ]
{\displaystyle p=0,\quad \sum _{i=m}^{i_{0}}\!\!{}^{0},円r^{i}={\cfrac {r^{i_{0}+0}}{(r-1)^{0}}}=r^{i_{0}},円}
{\displaystyle p=1,\quad \sum _{i=m}^{i_{1}}\!\!{}^{1},円r^{i}={\cfrac {r^{i_{1}+1}}{(r-1)^{1}}}-{\cfrac {r^{m}}{0!(r-1)^{1}}}={\cfrac {r^{i_{1}+1}-r^{m}}{r-1}},円}
{\displaystyle p=2,\quad \sum _{i=m}^{i_{2}}\!\!{}^{2},円r^{i}={\cfrac {r^{i_{2}+2}}{(r-1)^{2}}}-{\cfrac {r^{m+1}}{0!(r-1)^{2}}}-{\cfrac {r^{m}(i_{2}-m+1)}{1!(r-1)^{1}}}={\cfrac {{\cfrac {r^{i_{2}+2}-r^{m+1}}{r-1}}-r^{m}(i_{2}-m+1)}{r-1}},円}
{\displaystyle p=3,,円}
{\displaystyle \quad \sum _{i=m}^{i_{3}}\!\!{}^{3},円r^{i}={\cfrac {r^{i_{3}+3}}{(r-1)^{3}}}-{\cfrac {r^{m+2}}{0!(r-1)^{3}}}-{\cfrac {r^{m+1}(i_{3}-m+1)}{1!(r-1)^{2}}}-{\cfrac {r^{m}(i_{3}-m+1)(i_{3}-m+2)}{2!(r-1)^{1}}},円}
- {\displaystyle ={\cfrac {{\cfrac {{\cfrac {r^{i_{3}+3}-r^{m+2}}{r-1}}-r^{m+1}(i_{3}-m+1)}{r-1}}-{\tfrac {1}{2}}r^{m}(i_{3}-m+1)(i_{3}-m+2)}{r-1}},円}
{\displaystyle p=4,,円}
{\displaystyle \quad \sum _{i=m}^{i_{4}}\!\!{}^{4},円r^{i}={\cfrac {r^{i_{4}+4}}{(r-1)^{4}}}-{\cfrac {r^{m+3}}{0!(r-1)^{4}}}-{\cfrac {r^{m+2}(i_{4}-m+1)}{1!(r-1)^{3}}}-{\cfrac {r^{m+1}(i_{4}-m+1)(i_{4}-m+2)}{2!(r-1)^{2}}},円}
- {\displaystyle -{\cfrac {r^{m}(i_{4}-m+1)(i_{4}-m+2)(i_{4}-m+3)}{3!(r-1)^{1}}},円}
- {\displaystyle ={\cfrac {{\cfrac {{\cfrac {{\cfrac {r^{i_{4}+4}-r^{m+3}}{r-1}}-r^{m+2}(i_{4}-m+1)}{r-1}}-{\tfrac {1}{2}}r^{m+1}(i_{4}-m+1)(i_{4}-m+2)}{r-1}}-{\tfrac {1}{6}}r^{m}(i_{4}-m+1)(i_{4}-m+2)(i_{4}-m+3)}{r-1}},円}
{\displaystyle p=a,\quad \sum _{i=m}^{i_{a}}\!\!{}^{a},円r^{i}={r^{{i_{a}}+a} \over (r-1)^{a}}-\sum _{k=0}^{a-1}{r^{m+a-(k+1)}\prod _{j=1}^{k}(i_{a}-m+j) \over k!(r-1)^{a-k}},円}
{\displaystyle p=a+1,\quad \sum _{i=m}^{i_{(a+1)}}\!\!{}^{(a+1)},円r^{i}=\sum _{{i_{a}}=m}^{i_{(a+1)}}\left[\sum _{i=m}^{i_{a}}\!\!{}^{a},円r^{i}\right],円}
{\displaystyle =\sum _{{i_{a}}=m}^{i_{(a+1)}}\left[{r^{{i_{a}}+a} \over (r-1)^{a}}-\sum _{k=0}^{a-1}{r^{m+a-(k+1)}\prod _{j=1}^{k}(i_{a}-m+j) \over k!(r-1)^{a-k}}\right],円}
{\displaystyle =\sum _{{i_{a}}=m}^{i_{(a+1)}}\left[{r^{{i_{a}}+a} \over (r-1)^{a}}\right]-\sum _{{i_{a}}=m}^{i_{(a+1)}}\left[\sum _{k=0}^{a-1}{r^{m+a-(k+1)}\prod _{j=1}^{k}(i_{a}-m+j) \over k!(r-1)^{a-k}}\right],円}
{\displaystyle ={\sum _{{i_{a}}=m}^{i_{(a+1)}}\left(r^{{i_{a}}+a}\right) \over (r-1)^{a}}-\sum _{{i_{a}}=m}^{i_{(a+1)}}\left[\sum _{k=0}^{a-1}{r^{m+a-(k+1)}\left[{(i_{a}-m+k)! \over (i_{a}-m)!}\right] \over (r-1)^{a-k}\qquad k!}\right],円}
{\displaystyle ={r^{a}\sum _{{i_{a}}=m}^{i_{(a+1)}}\left(r^{i_{a}}\right) \over (r-1)^{a}}-\sum _{{i_{a}}=m}^{i_{(a+1)}}\left[\sum _{k=0}^{a-1}\left({r^{m+a-(k+1)} \over (r-1)^{a-k}}\right){i_{a}-m+k \choose k}\right],円}
{\displaystyle ={r^{a}\left({r^{i_{(a+1)}+1}-r^{m} \over r-1}\right) \over (r-1)^{a}}-\sum _{k=0}^{a-1}\left[\left({r^{m+a-(k+1)} \over (r-1)^{a-k}}\right)\sum _{{i_{a}}=m}^{i_{(a+1)}}{i_{a}-m+k \choose k}\right],円}
Shifting of starting and ending indices (see above for proof):
{\displaystyle ={r^{i_{(a+1)}+a+1}-r^{m+a} \over (r-1)^{a+1}}-\sum _{k=0}^{a-1}\left[\left({r^{m+a-(k+1)} \over (r-1)^{a-k}}\right)\sum _{i_{a}=k}^{i_{(a+1)}-m+k}{i_{a} \choose k}\right],円}
See combinations proof above:
{\displaystyle ={r^{i_{(a+1)}+a+1} \over (r-1)^{a+1}}-{r^{m+a} \over (r-1)^{a+1}}-\sum _{k=0}^{a-1}\left({r^{m+a-(k+1)} \over (r-1)^{a-k}}\right){i_{(a+1)}-m+k+1 \choose k+1},円}
Shifting of starting and ending indices (see above for proof):
{\displaystyle ={r^{i_{(a+1)}+a+1} \over (r-1)^{a+1}}-{r^{m+a} \over (r-1)^{a+1}}-\sum _{k=1}^{(a+1)-1}\left({r^{m+a-((k-1)+1)} \over (r-1)^{a-(k-1)}}\right){i_{(a+1)}-m+(k-1)+1 \choose (k-1)+1},円}
{\displaystyle ={r^{i_{(a+1)}+a+1} \over (r-1)^{a+1}}-{r^{m+a} \over (r-1)^{a+1}}-\sum _{k=1}^{(a+1)-1}\left({r^{m+a-k+1-1} \over (r-1)^{a-k+1}}\right){i_{(a+1)}-m+k \choose k},円}
Adding case k=0 to the summation, means that the same must be subtracted from the summation:
{\displaystyle ={r^{i_{(a+1)}+(a+1)} \over (r-1)^{(a+1)}}-{r^{m+a} \over (r-1)^{a+1}}-\left[\sum _{k=0}^{(a+1)-1}\left({r^{m+(a+1)-k-1} \over (r-1)^{(a+1)-k}}\right){i_{(a+1)}-m+k \choose k}-\left({r^{m+a} \over (r-1)^{a+1}}\right){i_{(a+1)}-m \choose 0}\right],円}
Terms cancel out.
{\displaystyle ={r^{i_{(a+1)}+(a+1)} \over (r-1)^{(a+1)}}-\sum _{k=0}^{(a+1)-1}\left({r^{m+(a+1)-(k+1)} \over (r-1)^{(a+1)-k}}\right){i_{(a+1)}-m+k \choose k},円}
{\displaystyle ={r^{i_{(a+1)}+(a+1)} \over (r-1)^{(a+1)}}-\sum _{k=0}^{(a+1)-1}{r^{m+(a+1)-(k+1)}\left[{(i_{(a+1)}-m+k)! \over (i_{(a+1)}-m)!}\right] \over (r-1)^{(a+1)-k}\qquad k!},円}
{\displaystyle \sum _{i=m}^{i_{(a+1)}}\!\!{}^{(a+1)},円r^{i}={r^{i_{(a+1)}+(a+1)} \over (r-1)^{(a+1)}}-\sum _{k=0}^{(a+1)-1}{r^{m+(a+1)-(k+1)}\prod _{j=1}^{k}(i_{(a+1)}-m+j) \over k!(r-1)^{(a+1)-k}},円}
Q.E.D.
First proof, used in second proof
[edit ]
{\displaystyle {\begin{aligned}n\geq m,&\sum _{i=m}^{n}\left[\sum _{j=m}^{i}{i-j+k \choose k}f(j)\right]&=&\sum _{j=m}^{m}{(m)-j+k \choose k}f(j)+\sum _{j=m}^{m+1}{(m+1)-j+k \choose k}f(j)\\&&&+\sum _{j=m}^{m+2}{(m+2)-j+k \choose k}f(j)+\cdots +\sum _{j=m}^{n-2}{(n-2)-j+k \choose k}f(j)\\&&&+\sum _{j=m}^{n-1}{(n-1)-j+k \choose k}f(j)+\sum _{j=m}^{n}{(n)-j+k \choose k}f(j)\\&&=&\left[{(m)-(m)+k \choose k}f(m)\right]+\left[{(m+1)-(m)+k \choose k}f(m)\right.\\&&&\left.+{(m+1)-(m+1)+k \choose k}f(m+1)\right]+\left[{(m+2)-(m)+k \choose k}f(m)\right.\\&&&\left.+{(m+2)-(m+1)+k \choose k}f(m+1)+{(m+2)-(m+2)+k \choose k}f(m+2)\right]\\&&&+\cdots +\left[{(n-2)-(m)+k \choose k}f(m)+{(n-2)-(m+1)+k \choose k}f(m+1)\right.\\&&&\left.+{(n-2)-(m+2)+k \choose k}f(m+2)+\cdots +{(n-2)-(n-4)+k \choose k}f(n-4)\right.\\&&&\left.+{(n-2)-(n-3)+k \choose k}f(n-3)+{(n-2)-(n-2)+k \choose k}f(n-2)\right]\\&&&+\left[{(n-1)-(m)+k \choose k}f(m)+{(n-1)-(m+1)+k \choose k}f(m+1)\right.\\&&&\left.+{(n-1)-(m+2)+k \choose k}f(m+2)+\cdots +{(n-1)-(n-3)+k \choose k}f(n-3)\right.\\&&&\left.+{(n-1)-(n-2)+k \choose k}f(n-2)+{(n-1)-(n-1)+k \choose k}f(n-1)\right]\\&&&+\left[{(n)-(m)+k \choose k}f(m)+{(n)-(m+1)+k \choose k}f(m+1)\right.\\&&&\left.+{(n)-(m+2)+k \choose k}f(m+2)+\cdots +{(n)-(n-2)+k \choose k}f(n-2)\right.\\&&&\left.+{(n)-(n-1)+k \choose k}f(n-1)+{(n)-(n)+k \choose k}f(n)\right]\\&&=&\left[{k \choose k}f(m)\right]+\left[{1+k \choose k}f(m)+{k \choose k}f(m+1)\right]\\&&&+\left[{2+k \choose k}f(m)+{1+k \choose k}f(m+1)+{k \choose k}f(m)\right]\\&&&+\cdots +\left[{n-2-m+k \choose k}f(m)+{n-3-m+k \choose k}f(m+1)\right.\\&&&\left.+{n-4-m+k \choose k}f(m+2)+\cdots +{2+k \choose k}f(n-4)\right.\\&&&\left.+{1+k \choose k}f(n-3)+{k \choose k}f(n-2)\right]\\&&&+\left[{n-1-m+k \choose k}f(m)+{n-2-m+k \choose k}f(m+1)\right.\\&&&\left.+{n-3-m+k \choose k}f(m+2)+\cdots +{2+k \choose k}f(n-3)\right.\\&&&\left.+{1+k \choose k}f(n-2)+{k \choose k}f(n-1)\right]\\&&&+\left[{n-m+k \choose k}f(m)+{n-1-m+k \choose k}f(m+1)\right.\\&&&\left.+{n-2-m+k \choose k}f(m+2)+\cdots +{2+k \choose k}f(n-2)\right.\\&&&\left.+{1+k \choose k}f(n-1)+{k \choose k}f(n)\right]\\&&=&f(m)\left[{k \choose k}+{1+k \choose k}+{2+k \choose k}\right.\\&&&\left.+\cdots +{n-2-m+k \choose k}+{n-1-m+k \choose k}+{n-m+k \choose k}\right]\\&&&+f(m+1)\left[{k \choose k}+{1+k \choose k}+{2+k \choose k}\right.\\&&&\left.+\cdots +{n-3-m+k \choose k}+{n-2-m+k \choose k}+{n-1-m+k \choose k}\right]\\&&&+f(m+2)\left[{k \choose k}+{1+k \choose k}+{2+k \choose k}\right.\\&&&\left.+\cdots +{n-4-m+k \choose k}+{n-3-m+k \choose k}+{n-2-m+k \choose k}\right]\\&&&+\cdots +f(n-2)\left[{k \choose k}+{1+k \choose k}+{2+k \choose k}\right]\\&&&+f(n-1)\left[{k \choose k}+{1+k \choose k}\right]+f(n)\left[{k \choose k}\right]\\&&=&\sum _{j=m}^{n}{n-j+k+1 \choose k+1}f(j)\end{aligned}},円}
{\displaystyle {\begin{aligned}n\geq m,\quad &\sum _{i=m}^{n}\left[\sum _{j=m}^{i}{i-j+k \choose k}f(j)\right]&=&\sum _{j=m}^{n}{n-j+k+1 \choose k+1}f(j)\\n=m,\quad &\sum _{i=m}^{m}\left[\sum _{j=m}^{i}{i-j+k \choose k}f(j)\right]&=&\sum _{j=m}^{m}{(m)-j+k \choose k}f(j)\\&&=&{m-(m)+k \choose k}f(m)={k \choose k}f(m)=f(m)={k+1 \choose k+1}f(m)\\&&=&{(m)-(m)+k+1 \choose k+1}f(m)=\sum _{j=m}^{m}{(m)-j+k+1 \choose k+1}f(j)\\n=x,\quad &\sum _{i=m}^{x}\left[\sum _{j=m}^{i}{i-j+k \choose k}f(j)\right]&=&\sum _{j=m}^{x}{x-j+k+1 \choose k+1}f(j)\\n=x+1,\quad &\sum _{i=m}^{x+1}\left[\sum _{j=m}^{i}{i-j+k \choose k}f(j)\right]&=&\sum _{j=m}^{x+1}{(x+1)-j+k \choose k}f(j)+\sum _{i=m}^{x}\left[\sum _{j=m}^{i}{i-j+k \choose k}f(j)\right]\\&&=&\sum _{j=m}^{x+1}{(x+1)-j+k \choose k}f(j)+\sum _{j=m}^{x}{x-j+k+1 \choose k+1}f(j)\\&&=&{(x+1)-(x+1)+k \choose k}f(x+1)\\&&&+\sum _{j=m}^{x}{(x+1)-j+k \choose k}f(j)+\sum _{j=m}^{x}{x-j+k+1 \choose k+1}f(j)\\&&=&f(x+1)+\sum _{j=m}^{x}{x-j+k+1 \choose k}f(j)+\sum _{j=m}^{x}{x-j+k+1 \choose k+1}f(j)\\&&=&f(x+1)+\sum _{j=m}^{x}\left[{x-j+k+1 \choose k}+{x-j+k+1 \choose k+1}\right]f(j)\\&&=&f(x+1)+\sum _{j=m}^{x}{x-j+k+2 \choose k+1}f(j)\\&&=&{(x+1)-(x+1)+k+1 \choose k+1}f(x+1)+\sum _{j=m}^{x}{(x+1)-j+k+1 \choose k+1}f(j)\\&&=&\sum _{j=m}^{x+1}{(x+1)-j+k+1 \choose k+1}f(j)\end{aligned}},円}
{\displaystyle {\begin{aligned}p\geq 1,\quad &\sum _{i=m}^{i_{p}}\!{}^{p}\ f(i)&=&\sum _{i=m}^{i_{p}}{i_{p}-i+p-1 \choose p-1}f(i)\\p=1,\quad &\sum _{i=m}^{i_{1}}\!{}^{1}\ f(i)&=&\sum _{i=m}^{i_{1}}{i_{1}-i \choose 0}f(i)=\sum _{i=m}^{i_{1}}f(i)\\p=s,\quad &\sum _{i=m}^{i_{s}}\!{}^{s}\ f(i)&=&\sum _{i=m}^{i_{s}}{i_{s}-i+s-1 \choose s-1}f(i)\\p=s+1,\quad &\sum _{i=m}^{i_{s+1}}\!{}^{s+1}\ f(i)&=&\sum _{i_{s}=m}^{i_{s+1}}\left[\sum _{i=m}^{i_{s}}\!{}^{s},円{\mathit {f}}(i)\right]\\&&=&\sum _{i_{s}=m}^{i_{s+1}}\left[\sum _{i=m}^{i_{s}}{i_{s}-i+s-1 \choose s-1}f(i)\right]\\&&=&\sum _{i=m}^{i_{s+1}}{i_{s+1}-i+(s+1)-1 \choose (s+1)-1}f(i)\\\end{aligned}},円}
Miscellaneous items (some valid, some not)
[edit ]
{\displaystyle {\begin{aligned}&=\sum _{i=m}^{i_{s+1}}f(i)\sum _{j=0}^{i_{s+1}-i}{j+s-1 \choose s-1}\\&=\sum _{i=m}^{i_{s+1}}f(i)\sum _{j=s-1}^{i_{s+1}-i+s-1}{[j-(s-1)]+s-1 \choose s-1}\\&=\sum _{i=m}^{i_{s+1}}f(i)\sum _{j=s-1}^{i_{s+1}-i+s-1}{j \choose s-1}\\&=\sum _{i=m}^{i_{s+1}}{i_{s+1}-i+(s+1)-1 \choose (s+1)-1}f(i)\end{aligned}},円}
{\displaystyle {\begin{aligned}&=\sum _{i=m}^{i_{s+1}}{i_{s+1}-i+s-1 \choose s-1}\sum _{j=m}^{i}f(j)\end{aligned}},円}
{\displaystyle f(x)={\dfrac {n-0}{h-0}}x+0={\dfrac {n}{h}}x,円}
{\displaystyle F(x)={\dfrac {n}{2h}}x^{2}+C,円}
{\displaystyle g(x)={\dfrac {n-b}{h-0}}x+b={\dfrac {n-b}{h}}x+b,円}
{\displaystyle G(x)={\dfrac {n-b}{2h}}x^{2}+bx+C,円}
{\displaystyle A_{f}=F(h)-F(0)=\left[{\dfrac {n}{2h}}(h)^{2}+C\right]-\left[{\dfrac {n}{2h}}(0)^{2}+C\right]={\tfrac {1}{2}}nh,円}
{\displaystyle A_{g}=G(h)-G(0)=\left[{\dfrac {n-b}{2h}}(h)^{2}+b(h)+C\right]-\left[{\frac {n-b}{2h}}(0)^{2}+b(0)+C\right]={\tfrac {1}{2}}nh-{\tfrac {1}{2}}bh+bh={\tfrac {1}{2}}nh+{\tfrac {1}{2}}bh,円}
{\displaystyle A=A_{g}-A_{f}=\left({\tfrac {1}{2}}nh+{\tfrac {1}{2}}bh\right)-\left({\tfrac {1}{2}}nh\right)=\mathbf {{\tfrac {1}{2}}bh} ,円}
{\displaystyle {\begin{aligned}&=(i_{k+1}-m+1){k-1 \choose k-1}\sum _{i=m}^{i_{k+1}}f(i)+(i_{k+1}-m){k \choose k-1}\sum _{i=m}^{i_{k+1}-1}f(i)\\&+(i_{k+1}-m-1){k+1 \choose k-1}\sum _{i=m}^{i_{k+1}-2}f(i)+\ldots +3{i_{k+1}-m+2+k-1 \choose k-1}\sum _{i=m}^{m+2}f(i)\\&+2{i_{k+1}-m+1+k-1 \choose k-1}\sum _{i=m}^{m+1}f(i)+{i_{k+1}-m+k-1 \choose k-1}\sum _{i=m}^{m}f(i)\end{aligned}},円}
これ、ちょっとちがうね。
{\displaystyle {\begin{aligned}&=f(m)\sum _{j=m}^{i_{k+1}}(i_{k+1}-j+1){j-m+k-1 \choose k-1}+f(m+1)\sum _{j=m}^{i_{k+1}-1}(i_{k+1}-j+1){j-m+k-1 \choose k-1}\\&+f(m+2)\sum _{j=m}^{i_{k+1}-2}(i_{k+1}-j+1){j-m+k-1 \choose k-1}+\ldots +f(i_{k+1}-2)\sum _{j=m}^{m+2}(i_{k+1}-j+1){j-m+k-1 \choose k-1}\\&+f(i_{k+1}-1)\sum _{j=m}^{m+1}(i_{k+1}-j+1){j-m+k-1 \choose k-1}+f(i_{k+1})\sum _{j=m}^{m}(i_{k+1}-j+1){j-m+k-1 \choose k-1}\end{aligned}},円}
{\displaystyle =\sum _{i=m}^{i_{k+1}}f(i)\sum _{j=0}^{i_{k+1}-i}(i_{k+1}-j-m+1){j+k-1 \choose k-1},円}
これもちがう。